ANALISIS KEPUASAN PENGGUNA PADA APLIKASI GO BALI GAS MENGGUNAKAN METODE PIECES FRAMEWORK - Arishanti, Putu Diva; Paramitha, Anak Agung Istri Ita; Putri, I Gusti Agung Pramesti Dwi (Politeknik Bisnis Indonesia, 2024)
This research aims to analyze user satisfaction with the Go Bali Gas application. The research design employed is quantitative research. The data sources include both secondary and primary data. The research sample consists of 89 users of the Go Bali Gas application, selected using the Slovin formula. The research methodology used in this study is the PIECES Framework, consisting of 6 variabels: Performance, Information and Data, Economics, Control and Security, Efficiency, and Service. Data collection began with the distribution of questionnaires to 89 users of the application. The collected data, categorized according to each variabel, was then calculated to determine the average for each variabel. The analysis results indicate that all six variabels, namely Performance, Information and Data, Economics, Control and Security, Efficiency, and Service, received very satisfactory ratings. Based on the analysis results, respondents provided suggestions for improvement in terms of payment methods, enhancement of features for tracking delivery notifications, offering free shipping, and improving overall user service.